MILITARY JARGON IN POINT BLANK VIDEO GAME: SEMANTIC ANALYSIS - Muhammad Faydullah (Nazharat: Jurnal Kebudayaan, 2022)
Jargon is special technical vocabulary associated with a specific area of work or interest. The researcher interests to discuss military jargon considering that in social terms, jargon helps to create and maintain connections among those who see themselves as insiders in some way and to exclude outsiders. This paper aims to discuss how many the military jargon found and its meaning, the semantic change, and the word formation process of military jargon in Point Blank Video Game. The researcher applied theory of semantic from George Yule as the grand theory. The design of this research is qualitative research and descriptive method. In the process of data collecting, the researcher used documentation technique. In the process of data analysing, the research used descriptive analysis technique. The results show that 1) there are 25 items which are categorized as military jargons. The meaning of jargon explained in conceptual meaning and associative meaning. 2) the semantic change that is experienced of military jargon in Point Blank Video Game. The researcher found 2 Specializations, 1 Generalization, and 6 Metonymy. 3) the word formation process of military jargon in Point Blank Video Game, the researcher found 1 Borrowing, 14 Compounding, and 6 Multiple Processes.